ANALISIS PENGARUH PENAMBAHAN WATER COOLING SYSTEM TERHADAP DAYA KELUARAN PANEL SURYA MENGGUNAKAN REFLECTOR - Nur Alfi Hidayati (2021)
Solar panels are tools that can be used to directly convert energy from sunlight into electrical energy. The use of a glass reflector (mirror) that is directed to the sun's rays can increase the irradiance value absorbed by the panel so that the panel surface becomes hot. In order for the solar panel to work properly, the solar panel requires cooling so that the surface of the solar panel does not overheat. The solar panel will experience a decrease in output power if it is too hot or exceeds the effective temperature limit, which is 30˚C to 50˚C. Therefore, to overcome this problem, this research is designed to take advantage of the excess heat generated by solar panels using a cooling system by immersing the heatsink into water (water cooling system) at the bottom of the solar panel surface. The test results showed that the solar panel output power decreased by 25.02-Watt for solar panels using reflectors and water-cooling systems and 27.30-Watts for solar panels with the addition of reflectors on the first day. And the second day with a value of 14.10-Watt for solar panels using reflectors and water-cooling systems and 16.20-Watts for solar panels using reflectors. From the results of testing and analysis of the use of a water-cooling system on solar panels, it is considered ineffective because the gap between the panel and the container is too small so that the heatsink used does not get air circulation which causes the heatsink and water to not absorb heat properly and become hot.